PP053 A Case Study: Collective Individual Basis For The Judiciary Debate. (2017) - Melo, Daniela; Trindade, Evelinda; Oliveira, Daniel; Martins, Patricia; Ribeiro, Lúcia
Abstract : INTRODUCTION: The volume of lawsuits for drugs has increased in Brazil. The scientific evidence basis consideration by the Brazilian judiciary system is being debated. In the State of São Paulo, the drug with the highest number of lawsuits is insulin glargine. Between January and August 2016, the São Paulo State Department of Health lost 264 insulin glargine lawsuits requiring supply for adult patients (>18 years old). Insulin glargine has already been submitted and unfavorably assessed by the Health Ministry SUS Technology Incorporation National Commission (CONITEC), so is not available in the Brazilian public system. METHODS: Random analysis of 153 (58 percent) lawsuits were carried out on digital court records. Data collected from legal proceedings were: the type of diabetes (1, 2 or unspecified); age of the patient; origin of the order; specialty of the prescriber and the reason described for the request. Each record was structured with variables data within a matrix in Microsoft Excel © software. Analysis of frequencies, absolute and relative distribution of quantitative variables, as well as conceptual clusters in the qualitative textual analysis are presented. RESULTS: The mean age of the 153 patients was 49±17 years. The majority of patients requested insulin glargine to achieve glycemic control (n = 116; 76 percent): because -"diabetes is uncontrolled and the analogous insulin is essential to get it" (n = 106; 69 percent); or -"patient claims to have obtained glycemic control with insulin glargine but there are none of the mandatory laboratory tests results in lawsuits" (n = 7; 5 percent); or -"ask replacement of insulin detemir with glargine for glycemic control" (n = 3; 2 percent). Only 87 (57 percent) lawsuits reported the patients diabetes type: type 1 (n = 42; 28% percent or 2 (n = 45; 29 percent). Most of this judicialization came from private outpatient clinics (n = 116; 76 percent) and 99 (65 percent) were prescribed by endocrinologists. CONCLUSIONS: Judicial decisions are still insufficiently underpinned by scientific evidence (only the patients drug needs claim has been recorded to justify supply) and are incomplete regarding objective diagnostic variables. Also, the judges awareness of interdisciplinary measures to achieve diabetic patients glycemic control, besides complementary drugs, may improve the Brazilian judicialization burden.